(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The use of digital forms at the Tasikmalaya City Department of Communication and Informatics was distributed across different platforms, resulting in decentralized data management and inefficient manual recapitulation. This study aimed to design and develop a web-based form builder application that supports centralized form creation, response collection, data management, and administrative reporting. The system was developed using the Waterfall model, consisting of problem identification and data collection, requirements analysis, system design, implementation, testing, and maintenance. Data were collected through observation, questionnaire-based needs elicitation, literature review, and documentation. The developed application provides authentication, dashboards, survey statistics, form management, a dynamic form builder, submission management, regional government organization management, access control, database backup, help documentation, and data export and import. The dynamic form builder enables authorized users to construct forms using configurable input components, including text, numerical, date, selection, checkbox, and file-upload fields, without developing a separate application for each data-collection requirement. Functional evaluation was conducted using Black Box Testing across 20 scenarios covering authentication, dashboards, form construction, field configuration, input validation, response submission, data management, access control, backup, export, import, and logout. All tested functions produced outputs consistent with the predefined requirements and were classified as passed. Preliminary User Acceptance Testing involving ten participants using super-admin access produced an overall mean score of 4.15 out of 5, equivalent to 83.0% of the maximum possible score, with a 100% positive-response rate. These findings indicate that the application successfully integrates the principal stages of form-data management within a single web-based platform and received a high level of initial user acceptance. However, further evaluation involving additional user roles, security testing, performance testing, and scalability assessment is required.